Radiosynthesis and Preclinical Evaluation of Bispecific PSMA/FAP Heterodimers for Tumor Imaging - Kongzhen Hu; Li Li; Yong Huang; Shimin Ye; Jiawei Zhong; Qingsong Yan; Yuhua Zhong; Lilan Fu; Pengju Feng; Hongsheng Li (MDPI AG, 2022)
Due to tumor heterogeneity and complex tumor-stromal interactions in multicellular systems, the efficiency of monospecific tracers for tumor diagnosis and therapy is currently limited. In light of the evidence of prostate-specific membrane antigen (PSMA) overexpression in tumor cells and fibroblast activation protein (FAP) upregulation in the tumor stroma, heterodimer dual targeting PSMA and FAP may have the potential to improve tumor diagnosis. Herein, we described the radiosynthesis, in vitro characterization, and micro-PET/CT imaging of two novel 18F-labeled bispecific PSMA/FAP heterodimers. 18F-labeled heterodimers showed high specificity and affinity targeting to PSMA and FAP in vitro and in vivo. Compared with the monospecific tracers [18F]AlF-PSMA-BCH and [18F]FAPI-42, both 18F-labeled heterodimers exhibited better tumor uptake in tumor-bearing mice. Their favorable characterizations such as convenient synthesis, high tumor uptake, and favorable pharmacokinetic profile could lead to their future applications as bispecific radiotracers for clinical cancer imaging.